Maya Intimacy with the Mountains: Pilgrimage, Sacrifice and Existential Economy - Jan Kapusta (Journal of Ethnology and Folkloristics)
In this paper, I present two very different and yet very similar ethnographic examples of mountain-related pilgrimage and sacrifice rituals performed by the present-day highland Maya. The question I ask is why the sense of sacredness, animation and power of the mountains endures among the traditionalist as well as Pentecostal Maya in spite of the extensive transformations of the world today. In so doing, I examine the native concept of the mountain not merely as a social or cultural representation, but as an expression of everyday lived experiences and existential relationships between people and the physical and spiritual world they inhabit. Finally, I argue that the experience of interaction, communication and intimacy between the Maya and their mountain deities can be best defined as a dynamic participation in the course of the world – an existential economy of ‘working the world’.